Establish Asean fund to help contain Rohingya crisis — analyst - Borneo Post, (KK) (Borneo Post, 2015)
KUALA LUMPUR: ASEAN members should set up a fund oil humanitarian grounds to help contain the crisis engulfing the Rohingya Muslim refugees, instead of leaving it to specific countries like Malaysia' to shoulder the burden, said a political analyst